Antigen Delivery Systems: Immunological and Technological Issues - Bruno Gander (2005)

(untitled)
This book series aims to provide a comprehensive survey of the many facets of drug delivery and targeting for senior undergraduates, graduates and established workers carrying out research in this area. Both drug delivery technologies and targeting grow in scope and potential, as well as complexity, almost daily. New opportunities arise through the development of new materials for the design and fabrication of drug delivery vehicles and carriers; new challenges are posed by the discovery and development of new therapeutic agents, which include not only small organic and inorganic molecules but also macromolecules that frequently have no natural propensity for transport across biological barriers.